Diabetic Ketoacidosis In Children With Type 1 Diabetes: Behavioral Patterns And Clinical Manifestation As Predictive Factors - Nusantara, Ana Fitria; Kusyairi, Achmad; Salam, Ainul Yaqin; Sulistiana, Eva (Chakra Brahmanda Lentera Institute, 2023)
Background: Type 1 Diabetes Mellitus (DM type 1) is occasionally becoming more common in Indonesia. According to the Indonesian Pediatrician Association (IDAI), as many as 1220 children in Indonesia had kind 1 DM in 2018. Lack of family education on type 1 DM might be fatal for sufferers. Diabetic ketoacidosis is one of the most prevalent side effects (DKA). Children can die if they do not receive care promptly. This study aims to detect behavioral trends and clinical manifestations in kids with type 1 diabetes to forecast the likelihood of developing DKA. Methods: A qualitative phenomenology-based research design was adopted for this study. Unstructured interviews were used to gather the data, which was analyzed using the Van Manen method. Twenty-four participants are selected by saturation when all participant's answers are similar. All data was collected by recording on devices for 45-60 minutes to interview each participant. Results: The findings revealed that the individuals' eating habits included consuming sugary drinks, buying prohibited items away from the house without their parent's knowledge, and eating portions that increased over time. Weight loss, frequent drinking, shortness of breath, and diminished consciousness are clinical symptoms. Conclusion: The sooner the patient receives assistance to prevent his condition from worsening, the sooner the symptoms and behavioral abnormalities can be recognized